Predicting the Future Need of Walking Device or Assistance by Moderate to Vigorous Physical Activity: A 2-Year Prospective Study of Women Aged 75 Years and Above. (20th June 2018) - Adachi, Takuji; Kamiya, Kuniyasu; Kono, Yuji; Iwatsu, Kotaro; Shimizu, Yuko; Honda, Ikumi; Yamada, Sumio
Abstract : Objective . To examine the association between daily moderate to vigorous physical activity (MVPA) and the change in mobility function among community-dwelling Japanese women aged 75 years and above. Methods . This prospective study included 330 older women aged 75 years and above who could walk without a walking device or assistance. MVPA and light-intensity physical activity (LPA) were assessed using an accelerometer for seven consecutive days. MVPA was defined as an activity with an intensity of >3 metabolic equivalents. The study outcome was a change in mobility function, defined as the need of walking device or assistance, during the two-year period. Results . The results of the logistic regression analysis showed that MVPA was inversely associated with a decline in mobility function after controlling for LPA and potential confounders (adjusted odds ratio (OR) = 0.93 per 1 min/d, 95% confidence interval (CI) = 0.88–0.99;P = 0.017), whereas LPA was not when adjusted for MVPA and confounders (adjusted OR = 0.99 per 1 min/d, 95% CI = 0.96–1.01;P = 0.245). The receiver operating characteristics analysis identified a 7.9 min/d of MVPA as the cut-off value. Conclusions . The results of this study suggest the importance of promoting daily MVPA for preventing mobility limitation in older women aged 75 years and above.